miR-199a-5p Represses Protective Autophagy and Overcomes Chemoresistance by Directly Targeting DRAM1 in Acute Myeloid Leukemia - Yang Li (Journal of Oncology, 2019)
Chemotherapy resistance is still a primary clinical obstacle to the successful treatment of acute myeloid leukemia (AML). The underlying mechanisms of drug resistance are complicated and have not been fully understood. Here, we found that miR-199a-5p levels were significantly reduced in refractory/relapsed AML patients compared to those who achieved complete remission after chemotherapy. Consistently, miR-199a-5p was markedly decreased in Adriamycin-resistant AML K562/ADM cells in contrast with Adriamycin-sensitive K562 cells, and its decrement dramatically correlated with the chemoresistance of AML cells. Furthermore, we demonstrated that the basic and Adriamycin-induced autophagic activity in K562/ADM cells was higher than that in K562 cells. This inducible autophagy played a prosurvival role and contributed to the development of acquired drug resistance. Importantly, we investigated that miR-199a-5p could negatively regulate autophagy, at least in part, by inhibiting damage regulator autophagy modulator (DRAM1) expression at both the transcriptional and posttranscriptional level. miR-199a-5p bound directly to the 3′-UTR of DRAM1 mRNA which was a functional target of miR-199a-5p. Indeed, downregulation of DRAM1 gene by siRNA in K562/ADM cells resulted in autophagy suppression and chemosensitivity restoration. These results revealed that the miR-199a-5p/DRAM1/autophagy signaling represented a novel pathway regulating chemoresistance, indicating a potential therapeutic strategy for the intervention in drug-resistant AML.